Paradigm of Legal Thought: Legal Prophetic Perspective - Fitrah Hamdani (Journal of Transcendental Law, 2020)
Objective: This article aims to discuss ‘criticism of legal prophetic paradigm against legal positivism paradigmMethodology: This research conducted a normative method used by legal positivists. This research is based on a philosophical approach as it is intended to explore the basic assumptions of the legal prophetic paradigm on the lack of the basic assumptions of the legal positivism paradigm.Findings: This paper will discuss the 'criticism of legal prophetic paradigm against legal positivism paradigm' using a philosophical approach as it is intended to explore the basic assumptions of the epistemology basis of the school of thought in legal science through comparison between the school of thoughts in legal science. The legal prophetic paradigm places moral as the main basis as its basic assumption. The verses of Allah and the Hadith of the Prophet regarding justice are the ontological basis of the Paradigm.Application of the Study: The object of legal science is human relations contained within (governed by) legal norms. Law science attempts to understand its object in a "legal" manner, which is from the legal perspective. Understanding something legally means understanding it as law, that is, as legal norms or as the content of legal norms or understanding something as determined by legal norms.Novelty/Originality: The prophetic paradigm can be approached through a Religion Science-based approach. The importance of this approach/religion science in understanding phenomenological law is none other but the occurrence of void or the broken links due to legal positivism thinking that is unable to play a functional role in presenting comprehensive legal justice. Keywords: Legal Positivism Paradigm, Legal Prophetic Paradigm, Basic Assumptions